Figure 5 in Killer sperm whale: a new basal physeteroid (Mammalia, Cetacea) from the Late Miocene of Italy - Bianucci, Giovanni; Landini, Walter (Zenodo, 2006)
Figure 5. Zygophyseter varolai gen. et sp. nov. Details (A–D) and lateral view (E) of the cranium of the holotype (MAUL 229/1). A, narial area in dorsal view; B, foramina and antorbital lamina of maxilla in dorsal view; C, left orbital area in ventral view; D, posteroventral surface. The vertical scale bar refers to A–D. Published as part of Bianucci, Giovanni & Landini, Walter, 2006, Killer sperm whale: a new basal physeteroid (Mammalia, Cetacea) from the Late Miocene of Italy, pp. 103-131 in Zoological Journal of the Linnean Society 148 (1) on page 110, DOI:10.1111/j.1096-3642.2006.00228.x, http://zenodo.org/record/5427349